Methodology of Islamic Studies: Islam as Religion (A Perspective Epistemology, Paradigm, and Methodology) - Adiyono, Adiyono; Ni'am, Syamsun; Akhyak, Akhyak (Analisis: Jurnal Studi Keislaman, 2024)
The study of methodology in Islamic studies has undergone a significant change from the traditional approach that focuses on textual and normative analysis to a more multidisciplinary and sophisticated paradigm. With the integration of epistemology, phenomenology, hermeneutics, and empirical techniques, the understanding of Islam as a religion now encompasses a broader social, cultural, and historical dimension. To achieve this goal, Systematic Literature Review (SLR) reviews are conducted using methodologies and tools that support systematic thinking, identification, feasibility testing, and meta-analysis through journal articles, books, research reports, and other sources published in the last 10 years. The Literature Selection and Quality Assessment consists of Inclusion Literature that discusses the Methodology of Islamic Studies: Islam as a Religion within the scope of Epistemology, Paradigm, and Methodology Perspectives from Google Scholar, Semantic Sholar, Eric, Crossref, and Science Direct databases. The results of the study found that the methodology of Islamic studies has shifted from a traditional approach to a more sophisticated and multidisciplinary paradigm. Epistemological shifts lead to contextual and interpretive perspectives, combining phenomenological, hermeneutical, historical, and empirical techniques. This approach allows for a more comprehensive understanding of Islam as a religion and a social phenomenon.